PERAN BALAI REHABILITASI SOSIAL DALAM PEMBINAAN MENTAL DAN PELATIHAN KETERAMPILAN KERJA PEREMPUAN MANTAN PEKERJA SEKS KOMERSIAL (STUDI KASUS DI BALAI REHABILITASI SOSIAL Ã¢â‚¬Å“WANITA UTAMAÃ¢â‚¬Â SURAKARTA) - Kurniawan, Hendra Setya (Unnes Civic Education Journal, 2017)
Abstract: The purpose of this study is to assess the role of the Social Rehabilitation Center "Wanita Utama" Surakarta in mental development and job skills training, and supporting and inhibiting factors in mental development and job skills training female former commercial sex workers. This research used Qualitative method of collecting data through observation, interviews, and documentation. The research location is the Social Rehabilitation Center "Wanita Utama" Surakarta. Based on the research results, it can be concluded that the role of the Center for Social Rehabilitation Ã¢â‚¬Å“Wanita UtamaÃ¢â‚¬Â Surakarta in mental development and job skills training as a social planner's role, the role of liaison, the role of educators, and the role of empowerment. In mental development type of activities includes: coaching Islam and Christianity, mental counseling, character, character development, and ESQ. While the job skills training includes skills cooking/catering, sewing, and salon. Inhibiting factors in mental development and job skills training comes from the Beneficiary, derived from the Social Rehabilitation Center Ã¢â‚¬Å“Wanita UtamaÃ¢â‚¬Â Surakarta, and comes from the Community. Supporting factors, derived from internal and external supporters. Internal supporting factorsnamely human resources, and education. External support factor is the availability of APBD 1 Central Java as a source of funds, and support cross-sectoral cooperation are good. The writer suggested that, (1) should provide guidance module on mental and job skills training, so that beneficiaries can learn about their own material after hours of coaching. (2) Added the tool cooking skills, sewing, and the salon so the training is effective. (3).At the time of visiting hours should cooperate with the police so that no disruption of the family, pimp, or thugs who want to forcibly eject Beneficiaries